Socio-economic performance of Bt eggplant cultivation in Bangladesh - Rashid, MA; Hasan, MK; Matin, MA (Bangladesh Journal of Agricultural Research, 2018)
A study was conducted in 35 districts of Bangladesh during 2016-17 winter season for assessing the farm level performance of Bt eggplant in reducing pesticide use, cultivation cost and increase farm income. Five hundred five Bt eggplant farmers were selected purposively and 350 non-Bt eggplant farmers were selected randomly for the study. Net returns per hectare were Tk. 179,602/ha for Bt eggplant as compared to Tk. 29,841/ha for non-Bt eggplant. Pesticides were applied 11 times to Bt eggplant where as it was 41 times to non-Bt eggplant for controlling sucking pests. The Bt eggplant farmers saved 61 percent of the pesticide cost compared to non-Bt eggplant farmers, experienced no losses due to fruit and shoot borer, and received higher net returns. The experience with Bt eggplant technology was good for most of the locations and up to the mark and off course this technology will be significantly improved to their socio-economic conditions in future as reported by the Bt respondents. All Bt and 86% non-Bt farmers wanted to cultivate Bt eggplant in the next year if they can obtain the seeds/seedlings from the research station. For getting higher yield and economic benefits, in the course of technology dissemination, the importance of good production practices must be emphasized. Bangladesh J. Agril. Res. 43(2): 187-203, June 2018